Phospholipase Dα1 mediates the high-Mg2+ stress response partially through regulation of K+ homeostasis - Kocourková, Daniela; Krčková, Zuzana; Pejchar, Přemysl; Kroumanová, Kristýna; Podmanická, Tereza; Daněk, Michal; Martinec, Jan (Plant, cell & environment, 2020)
Intracellular levels of Mg2+ are tightly regulated, as Mg2+ deficiency or excess affects normal plant growth and development. In Arabidopsis, we determined that phospholipase Dα1 (PLDα1) is involved in the stress response to high-magnesium conditions. The T-DNA insertion mutant pldα1 is hypersensitive to increased concentrations of magnesium, exhibiting reduced primary root length and fresh weight. PLDα1 activity increases rapidly after high-Mg2+ treatment, and this increase was found to be dose dependent. Two lines harbouring mutations in the HKD motif, which is essential for PLDα1 activity, displayed the same high-Mg2+ hypersensitivity of pldα1 plants. Moreover, we show that high concentrations of Mg2+ disrupt K+ homeostasis, and that transcription of K+ homeostasis-related genes CIPK9 and HAK5 is impaired in pldα1. Additionally, we found that the akt1, hak5 double mutant is hypersensitive to high-Mg2+ . We conclude that in Arabidopsis, the enzyme activity of PLDα1 is vital in the response to high-Mg2+ conditions, and that PLDα1 mediates this response partially through regulation of K+ homeostasis.
Keywords: fyziologický stres; proteiny huseníčku; fosfolipasa D; draslík; hořčík; Potassium; high magnesium; Blotting, Western; phospholipase D; Arabidopsis thaliana; Arabidopsis Proteins; HAK5; Stress, Physiological; Arabidopsis; homeostáza; ion homeostasis; Homeostasis; transkriptom; Transcriptome; western blotting; Magnesium; CIPK9; potassium; Phospholipase D